Production and characterization of transgenic Arabidopsis and soybean (Glycine max (L.) Merrill.) plants over-expressing oryzacystatin I (OC-I) - Kunert, Karl J. (University of Pretoria, 2015)
Thesis (PhD)--University of Pretoria, 2014.